Priority-based routing in a campus network using SDN - Lara Petitdemange, Adrián (2017)
In this paper we propose an SDN-based control plane for the University of Costa Rica. Our campus network faces heavy congestion problems and fails at providing adequate quality of service (QoS). Therefore, we describe a solution that leverages priority-traffic routing to ensure that important services (such as live video streaming) are not as heavily affected by congestion. To this end, we first survey how SDN has been used in campus networks. Next, we model and solve a linear programming problem to find the optimal solution to our priority-based routing problem. After that, we propose two alternative network designs that could be used to implement QoS in our campus network. We then propose a priority-based routing algorithm and compare the performance of the prototype against the optimal results by emulating the campus network on Mininet. We show how our design is capable of QoS for high-priority traffic in realistic conditions. Likewise, we also show the advantages of having a fully-SDN network capable of per-flow traffic throttling to maximize link usage.